Accelerated synthesis of 3-dihydroquinazolin-4(1H)-one derivatives using nano-SiO2-SO3H as an efficient acidic catalyst - Habyl Naeemi; Nasrin Shadjou; Mehdi Mahmoudian (Scientific Reports)
Abstract 2,3-dihydroquinazolin-4(1H)-one derivatives are recognized as vital compounds in medicinal chemistry due to their diverse biological activities, making them valuable for pharmaceutical research and therapeutic applications. Hence, the rapid and accurate synthesis of these derivatives need efficient nano-catalysts. The study outlines the preparation of nano-SiO2-SO3H through the covalent attachment of sulfonic acid groups to silica nanoparticles. Then, this material is applied as a catalyst for the efficient one-pot synthesis of 2,3-dihydroquinazolin-4(1H)-one derivatives. The reaction involves isatoic anhydride, an aromatic aldehyde, and ammonium acetate, directed under solvent-free conditions at a temperature of 110 °C. Also, the prepared catalyst characterized using Field Emission Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy (TEM) for morphological analysis, Fourier Transform Infrared Spectroscopy (FT-IR) for functional group identification, and Energy Dispersive X-ray Spectroscopy (EDAX) for its elemental composition. The presence of sulfonic acid groups as a Brønsted acids, enhance the catalytic properties of the silica nanoparticles and facilitate the reaction between the reactants in synthesis process and make the designed catalyst as a suitable candidate for promoting the 2,3-dihydroquinazolin-4(1H)-one synthesis. This synthesis protocol offers a sustainable and eco-friendly approach, eliminating the use of toxic solvents. It provides significant advantages compared to previously reported methods, such as using of nontoxic, green, and stable nanocatalyst. Additionally, the catalyst is easily recoverable and reusable, the reactions proceed under solvent-free conditions, and the process characterized by short reaction times (5–20 min). Furthermore, it achieves excellent yields ranging from 85 to 98% and features a simple workup procedure, making it highly relevant for advancing environmental chemistry practices.